New Directions for Refugee Determination and Protection in Canada - Aiken, Sharryn (Refuge: Canada's Journal on Refugees, 1999)
This article is a review and analysis of theCanadian government's recent "whitepaper" on immigration and refugeepolicy and legislation. This review focuseson the proposals related to inlandrefugee determination and protection.While noting a number of positive initiativesin the document, the author expressesconcern about the future ofCanada's role in refugee protection in thenext millennium.